Preparation of CsPb(Cl/Br)3/TiO2:Eu3+ composites for white light emitting diodes - Zhang, Chen; Wang, Minqiang; Shi, Jindou; Wang, Junnan; Da, Zheyuan; Zhou, Yun; Xu, Youlong; Gaponenko, Nikolai V.; Bhatti, Arshad Saleem (Frontiers in Chemistry, 2023)
The inherent single narrow emission peak and fast anion exchange process of cesium lead halide perovskite CsPbX3 (X = Cl, Br, I) nanocrystals severely limited its application in white light-emitting diodes. Previous studies have shown that composite structures can passivate surface defects of NCs and improve the stability of perovskite materials, but complex post-treatment processes commonly lead to dissolution of NCs. In this study, CsPb(Cl/Br)3 NCs was in-situ grown in TiO2 hollow shells doped with Eu3+ ions by a modified thermal injection method to prepare CsPb(Cl/Br)3/TiO2:Eu3+ composites with direct excitation of white light without additional treatment. Among them, the well-crystalline TiO2 shells acted as both a substrate for the dopant, avoiding the direct doping of Eu3+ into the interior of NCs to affect the crystal structure of the perovskite materials, and also as a protection layer to isolate the contact between PL quenching molecules and NCs, which significantly improves the stability. Further, the WLED prepared using the composites had bright white light emission, luminous efficiency of 87.39 lm/W, and long-time operating stability, which provided new options for the development of perovskite devices.